Studies on coastal dwelling Islamic communities in Taluksangay, Zamboanga City, Philippines - Yap, David Leonides T. (2012)
In Philippine coastal Islamic communities, there are quite a number of building practices and beliefs done which are not written in the Quran. These indicate that most of the current beliefs and practices related to settlement and house building are more of a folk tradition rather than Islamic. What transpired in the Philippines was an absorption and adaptation of Islam into the culture rather than a replacement of longstanding practices. The study examines how Folk Islam is manifested in settlement patterns and housing forms.
Keywords: Datar, Francisco A; Tanoue, kenichi; Dwellings -- Taluksangay(Zamboanga City); Superstition -- Taluksangay ( Zamboanga City)